Consideration of racism experiences in the implementation of trauma‐focused therapy in primary care. (20th May 2022) - McCuistian, Caravella; Kimball, Sarah L.; Buitron de la Vega, Pablo; Godfrey, Laura B.; Fortuna, Lisa R.; Valentine, Sarah E.
Abstract: Objective: To understand providers' perceptions of how a patient's experience of racism may impact the successful implementation of a brief posttraumatic stress disorder (PTSD) treatment in the safety net integrated primary care setting. To conduct a developmental formative evaluation prior to a hybrid type I effectiveness‐implementation trial. Data Sources and Study Setting: From October 2020 to January 2021, in‐depth qualitative interviews were conducted with integrated primary care stakeholders ( N  = 27) at the largest safety net hospital in New England, where 82% of patients identify as racial or ethnic minorities. Study Design: Interviews with clinical stakeholders were used to (a) contextualize current patient and provider experiences and responses to racism, (b) consider how racism may impact PTSD treatment implementation, (c) gather recommendations for potential augmentation to the proposed PTSD treatment (e.g., culturally responsive delivery, cultural adaptation), and (d) gather recommendations for how to shift the integrated primary care practice to an antiracist framework. Data Collection/Extraction Methods: Interview data were gathered using remote data collection methods (video conferencing). Participants were hospital employees, including psychologists, social workers, primary care physicians, community health workers, administrators, and operations managers. We used conventional content analysis. Principal Findings: Clinical stakeholders acknowledged the impact of racism, including racial stress and trauma, on patient engagement and noted the potential need to adapt PTSD treatments to enhance engagement. Clinical stakeholders also characterized the harms of racism on patients and providers and provided recommendations such as changes to staff training and hiring practices, examination of racist policies, and increases in support for providers of color. Conclusions: This study contextualizes providers' perceptions of racism in the integrated primary care practice and provides some suggestions for shifting to an antiracist framework. Our findings also highlight how racism in health care may be a PTSD treatment implementation barrier.